A small molecule with a big scissoring effect: sodium dodecyl sulfate working on two-dimensional metal–organic frameworks. Issue 6 (29th January 2021) - Luo, Qing; Ding, Zhen; Sun, Huamin; Cheng, Zhen; Shi, Naien; Song, Chuanyuan; Han, Min; Gu, Daqing; Yi, Mingdong; Sun, Yujie; Xie, Linghai; Huang, Wei
Abstract : In this paper, a SDS-directed solution method was developed to synthesize a series of well-dispersed two-dimensional non-layered metal–organic frameworks (MOFs) (ZIF-8 & ZIF-67) and layered MOFs (ZnTCPP & CuBDC). Abstract : Ultrathin two-dimensional (2D) metal–organic framework (MOF) nanosheets are promising advanced materials due to their particularly thin thickness and exposed active sites. The difficulty in the controlled synthesis of 2D MOFs and the limited effective synthetic routes greatly limit further extension of their applications. In this work, a solution-processed approach based on the direction of sodium dodecyl sulfate (SDS) is developed, by which a series of well-dispersed square non-layered MOF and layered MOF nanosheets have been synthesized successfully. Dynamic light scattering analysis suggests that the negative charge of SDS induces the pre-assembly of metal ions, which further leads to the 2D self-assembly process in the growth of MOF nanocrystals. The approach would be sure to push forward the effective shape control and mass production of MOF 2D nanomaterials and stimulate further research in the fields of electronic nanodevices, energy storage, catalysis and biosensing.